2012
DOI: 10.1159/000341708
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Rollerball Endometrial Ablation in the Management of Refractory Recurrent Symptomatic Endometrial Hyperplasia without Atypia

Abstract: Backgrounds: Menorrhagia – heavy, extended or irregular menstruations – may be associated with endometrial hyperplasia. The aim of this study was to evaluate the clinical efficacy and safety of transcervical rollerball endometrial ablation (EA-R) and to discuss surgical outcomes in patients with simple endometrial hyperplasia without atypia who have had a history of medical treatment failure or recurrence. Methods: A prospective study was designed. Thirty women underwent EA-R. Preoperative and postoperative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, the alteration, role, and interaction of apoptotic signals in EH are unclear. Some studies that focused on endometrial carcinoma showed that the apoptotic signal is important in its development [18,19]. EH is the prelude of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the alteration, role, and interaction of apoptotic signals in EH are unclear. Some studies that focused on endometrial carcinoma showed that the apoptotic signal is important in its development [18,19]. EH is the prelude of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal uterine bleeding (AUB), which is the leading cause of gynecological visits, leads to anemia, fatigue and syncope due to blood loss, and has a negative impact on women's quality of life, daily activities and psychosocial life [1]. Also, it is the most common and the earliest symptom of endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%